Enhancing Critical Thinking Skills for Army Leaders Using Blended-Learning Methods - Straus, Susan G. (RAND Corporation, 2013)
The U.S. Army's Command and General Staff School offers its Advanced Operations Course (AOC) for junior field-grade officers using both traditional resident instruction and a model referred to as blended distributed learning (BDL). This report assesses the effectiveness of AOC-BDL based on student and graduate surveys and identifies best practices for BDL from empirical research and case studies.